Mapping multiple wild pig species’ population dynamics in Southeast Asia during the African Swine Fever outbreak (2018–2024) - Lieb, Zoë E.; Meijaard, Erik; Brodie, Jedediah F.; Shabrani, Adi; Mohd-Azlan, Jayasilan; Supriatna, Jatna; Struebig, Matthew John; Deere, Nicolas J.; Spencer, Katie L.; Heon, Suipeng; Wong, Lok Jinn; Juiling, Suzika; et al. (Wiley-Blackwell Publishing, 2025)
The 2018 arrival of African swine fever (ASF) in China was followed by reports of wild pig deaths across most countries in Southeast Asia. However, the magnitude and duration of population-level impacts of ASF on wild pig species remain unclear. To elucidate the spatiotemporal spread of ASF in the region for native pig species, we gathered qualitative information on wild pig population dynamics in Southeast Asia between 2018 and 2024 from 88 expert elicitation questionnaires representing sites in 11 countries. Peak reported population declines occurred in 2021 and 2022, with more than half of respondents reporting declining wild pig populations, far higher than in earlier years. The reported declines waned to 44.23% in 2024, whereas simultaneously, the number of populations reported to be “increasing” increased from 11.3%–13.2% in 2019–2022 to 28.9% in 2024. These reports suggest that the ASF outbreak may have peaked for wild boars and bearded pigs in mainland Southeast Asia, Borneo, and Sumatra, with some subsequent recovery. However, the disease is still expanding into the ranges of island endemic species, such as new reports for the Sulawesi warty pig (Sus celebensis) in September of 2024. Island endemics remain particularly vulnerable to extinction from ASF and require urgent monitoring and conservation action.